Predictive Contribution of Personality Traits in a Socio-Cognitive Model of Academic Performance in Mathematics - Cupani, Marcos (2013)
Social Cognitive Career Theory (SCCT) explains academic performance as a function of conceptually distinct and interrelated cognitive variables. We aimed at extending SCCT?s performance model by examining the direct and indirect ? through socio-cognitive variables - contribution of personality traits on mathematics academic performance. Argentine youths (N = 543) were assessed in mathematics self-efficacy, outcome expectations, performance goals and skills. Personality traits were assessed through the Big Five Questionnaire for Children. Path analyses indicated that the contribution of personality on academic performance was mediated by socio-cognitive mechanisms. The results suggested that (a) students who exhibited higher Conscientiousness scores had higher self-efficacy beliefs and more positive outcome expectations and set more demanding performance goals, and (b) students who had higher Openness/Intellect scores exhibited higher self-efficacy beliefs. Gender did not moderate the relations among cognitive variables but influenced the association between personality traits and cognitive variables. Implications for teachers and guidance counselors are discussed.